Behavioral Factors Related to Musculoskeletal Disorders in Nurses based on Theory of Planned Behavior - Imanzad, masoumeh; Gharlipour, zabihollah; Kohpaie, alireza; Mohebi, siamak; Arsang gang, shahram; Sayyarpour, mostafa; Gilasi, hamidreza; Mashkuri, alireza; Pahlevani, soheila; Ahmadi, hadiseh; Heidari, sakineh; Akbari, zahra (Advances in Nursing & Midwifery, 2014)
Abstract Introduction: Musculoskeletal disorders are the most common and costly occupational injuries. Musculoskeletal disorders represent a significant occupational problem among nurses. The aim of current study was to determine behavioral factors related to musculoskeletal disorders among nurses by using the theory of planned behavior. Methods: A cross-sectional study was carried out among nurses in hospitals of Qom University of Medical Sciences in 2011. A total number of 264 registered nurses with working experience at least one year , and different shifts were included in the study. A reliable and valid questionnaire based on the theory of planned behavior and Nordic was used for data gathering. Data were analyzed using statistical software SPSS for windows V.16 Independent t-test, chi-square, Mann - Whitney and Pearson correlation tests were used for testing the correlations among variables. Results: The study showed that 47.5% of nurses in the past 12 months and 36.2% during the past 7 days have suffered from musculoskeletal disorders. The most work-related disorders were in the low back and neck. Also statistically significant difference was found between the mean scores of the constructs of attitude, subjective norm, perceived behavioral control and behavioral intention in nurses with and without musculoskeletal disorders. Conclusion: Musculoskeletal disorder rate still is high in nurses and attention and action is needed to improve nurses’ health. Theory of planned behavior is effective at identifying behavioral and attitudinal factors related to the correct ergonomic principles in the through working position. Key words: Musculoskeletal disorders, Nurses, Theory of planned behavior REFERENCES Ajzen I (2011). The theory of planned behaviour: reactions and reflections . Psychology and Health. 26(9) 1113-2. Alexopoulos EC, B. A.(2003). Risk factors for musculoskeletal disorders among nursing personnel in Greek hospitals . Int Arch Occup Environ Health.76(4) 289-94. Andersson GBJ (1999). Epidemiological features of chronic low-back pain . Lancet, 354(9178)581-5. Armitage C J, C(2001). "Efficacy of the theory of planned behavior: a meta-analytic review". British Journal of Social Psychology , 40(pt 4) 471-499. Armitage CJ, A. M(2002). "Exploring discontinuity patterns in the trans-theoretical model: An application of the theory of planned behavior". British Journal of Health Psychology 7(pt 1) 89-103. Armitage CJ, C. M(2000). "Social cognition models and health behavior: A structured review". Psychology and Health , 15(2) 173-89. Arnold J et all (2006). "How well can the theory of planned behavior account for occupational intentions". Journal of Vocational Behavior , 69(3) 374–390. نشریه دانش ده پرستاری و مامایی ت سپ ن لضا تل کس ا للت ا ب ط ت م یر فتا ملاع / 9 ع ر و ی ب ا ا ر ا ی ک ا ر خ ت Bilski B(2004). "Determinants of musculoskeletal system load and their health effects among nurses from four Poznan hospitals". Med Pr , 55(5) 411-16. Botha R(1998). "Anthropometric variability, equipment usability and musculoskeletal pain in a group of nurses in the Western Cape". Appl Ergon 29(6) 481-90. Carroll A(2003). "Predicting chronic back pain suffers’ intention to exercise". British Journal of Therapy and Rehabilitation 10(2)53-8. Cdc(1997). NIOSH: National Institute for Occupational Safety and Health. Bernard BP. Musculoskeletal disorders and workplace factors: A critical review of epidemiologic evidence for work-related musculoskeletal disorders of the neck, upper extremity, and low back. [cited 1997 July], Available from: http://www.cdc.gov/niosh/97-141pd.html, 97-141. Chiou YH (1994). "Epidemiology of low back pain in Chinese nurses". Int J Nurs Stud , 31(4) 361-368. Choobineh A (2003). Posture evaluation methods in occupational ergonomic 1st ed. Tehran: Fanavaran Publisher., 10-15[Persian]. Choobineh A(2007). "Perceived demands and musculoskeletal disorders among hospital nurses". Hakim Research Journal 10(2)70- 75 [Full Text in Persian]. Converso A(2004). Winning the battle against back injuries RN , 67, 52-7. Dunstan C, Tyson GA (2013). What leads to the expectation to return to work? Insights from a Theory of Planned Behavior (TPB) model of future work outcomes. Work, 46(1) 25-37. FerreiraERREIRA. R, Fonseca J, Rotenbergl L(2012). "A multifactorial approach to sickness absenteeism among nursing staff". Rev Saude Publica , 46(2) 259-68. Feye P(2000). "The role of physical and psychological factors in occupational low back pain:a prospective cohort study". Occupational and Environmental Medicine , 57(2)116-20. Jacquline V(2004). "Studies now address the relationship between long working musculoskeletal disorders among nursing personnel". Caring for the ages , 5, 34-35. Jenner, W(2002). "Explaining hand hygiene practice: An application of the theory of planned behavior". Psychology Health & Medicine 7(3) 311-26. Johnson A(2005). "The prediction of safe lifting behavior: An application of the theory of planned behavior". Journal of Safety Research , , 36(1) 63-73. Johnsson K, Kjellberg A, LagerstromM(2004). A direct observation instrument for assessment of nurses patient transfer technique. Appl Ergon, 35(6) 591-601. Juibaril A, Farrokhi N(2010). "The relationship between knowledge of ergonomic science and the occupational health among nursing staff affiliated to Golestan University of Medical Sciences". Iran J Nurs Midwifery Res , 15(4) 185–189[Full Text in Persian]. Kaushik N(2008). Effect of Body Posture on Stress Experienced by Worker Stud Home Comm Sci 2, 1-5. Kony S et all(2011). Intention to comply with post-exposure management among nurses exposed to blood and body fluids in Taiwan: application of the theory of planned behavior. Journal of Hospital Infection 77(4) 321-6. Konz S(1999). Posture Biomechanics Ergonomics In: Shrawan Kumar 3st ed. London: Taylor and Francis,, 309-14. Kortteisto M, Komulainen J, Mantyranta T, Rissanen P (2010). "Healthcare professionals’ intentions to use clinical guidelines: a survey using the theory of planned behaviour". Implement Sci, 5, 51.. doi: 10.1186/1748- 5908-5-51. Kroemer K(2001). Body postures. International encyclopedia of human factors and ergonomics, Second edition. London and New York: Taylor and Francis Inc,, 1378. Magnago S, Griep R, Analck, Camponogara S(2010). Nursing workers: Work conditions, social-demographic characteristics and skeletal muscle disturbances . Acta Paul Enferm 23(6) 187-93. Malone R(2000). "Ergonomics, policy , and the ED nurse". J Emerg Nurs. , 26(5) 514-15. 1392 ناتسبات ،81 هرامش ،23 هرود / 10 ناراکمه و دازنامیا هموصعم Maul I , Klipstein A, Krueger H (2003). "Course of low back pain among nurses: a longitudinal study across eight years". Occup Environ Med , 60(7) 497-503. Mehrdad R, , Haghighat M, Aminian O(2010)." Association between psychosocial factors and musculoskeletal symptoms among Iranian nurses". Am J Ind Med 53(10) 1032-39. Meier E(2001). Ergonomic standard and implication for nursing Nursing Economic ., 19(1) 31-2. Menzel N(2004). "Back pain prenalence in nursing personnel: measurement issusues". AAOHN Journal , 52(2) 54-65. Menzel N , Bernard T, Nelson A (2004). "The physical workload of nursing personnel: association with musculoskeletal discomfort". Int J Nurs Stud , 41(8) 859-67. Mohammadi zeydi H et all(2009). "The Prediction of Adoption with Correct Sitting Postural Habit: An Application of the Theory of Planned Behavior". European Journal of Scientific Research , 28(2) 205-214. Mohseni bandpey M(2006). "Ahmad Shirvani M, Bagheri Nesami M, Khalilian AR. Risk factors for low back pain in nurses". Journal of Mazandaran University of Medical Sciences , 15(17) 118-124[Full Text in Persian]. MUROFUSE NT, M. M. 2005. "Diseases of the osteomuscular system in nursing workers". Rev Latinoam Enferm , 13, 264-73. Nasiri F, Nakhaei N, Kazemi N (2005). "Lower limb varicose veins and their relationship with risk factors in nurses of the Birjand University of Medical Sciences hospitals". Journal of birjand university of medical sciences , 12, 9-15. [Full Text in Persian]. Nasl Saraji J, Shahtaheri SJ, Golbabaei F (2005). Sciences, 18(1) 61-67 [Full Text in Persian]. Nelson G, Menzel N (2003). "Myths and facts about back injuries in nursing". Am J Nurs , 103(2) 32-40. NordinG, Pope MH (1997). Musculoskeletal disorder in the workplace. Principles and practice 1st ed. St Louis: Mosby-Year Book Inc., 211-40. Norman P (1995). "Managers’ intentions to be assessed for national vocational qualifications: an application of the theory of planned behavior". Social Behavior and Personality , 23(1) 59–67. Nussbam N (2001). "Effect of training in modifying working methods during common patient handling activities". Int Ergon 27, 33-41. Omokhodion F , Ogonnow BE (2000). Prevalence of low back pain among staff in a rural hospital in Nigeria. Occup l Med 50, 107-110. OzgoliI G et all (2006). Musculoskeletal Symptoms AssessmentAmong Midwives, Hamedan , 2002. Iran Occupational Health Journal , 3, 37-42 [Full Text in Persian]. Quine L, Arnold A(1998). Predicting and understanding the use of safety helmet use among schoolboy cyclists: A comparison of the theory of planned behavior and the health belief model. Psychology and Health., 13(7) 251-69. Rahimi A, Akhoond MR (2006) "An investigation into the prevalence of vertebral column pains among the nurses employed in Hamedan hospitals". Razi Journal of Medical Sciences , 13(51) 105-114 [Full Text in Persian]. Rundmo T(2001). "Employee’s images of risk". Journal of Risk Research . , 4(4) 393-404. RUTTER DR, Q., ALBERY IP, 1998. "Perceptions of risk in motorcyclists: Unrealistic optimism, relative realism and predictions of behavior". British Journal of Psychology . , 89, 681-96. Sikir L(2010). "Prevalence and risk factors of low back pain among nurses in a typical Nigerian hospital". Afr Health Sci 10(1) 26-30. Smedley J Egger P, Cooper C et all (1995). "Manual handling activities and risk of low back pain in nurses". Occupational and Environmental Medicine 52(3) 160-63. Smith M, MiyajimaT, MizutaniT (2003). "Musculoskeletal disorders self reported by female nursing students in central Japan: a complete cross sectional survey". Int J Nurse Stu , 40(7) 725-29. Smithdr N, Kang, Wang RS(2004). "Musculoskeletal disorders among professional nurses in mainland China". نشریه دانش ده پرستاری و مامایی ت سپ ن لضا تل کس ا للت ا ب ط ت م یر فتا ملاع / 11 ع ر و ی ب ا ا ر ا ی ک ا ر خ ت J Prof Nurs , 20(6) 390-95. Tinubu. C, Oyeyemi AL , Fabunmi A(2010). Work-Related Musculoskeletal Disorders among Nurses in Ibadan, South-west Nigeria: a cross-sectional survey. Musculoskelet Disorders. 11, 12 http://www.biomedcentral.com/1471-2474/11/12. Trinkoff J, Gelger J, Storr CL(2003). "Perceived physical demands and reported musculoskeletal problems in registered nurses". Am J prev Med , 24(3) 270-275. Zakeriyan M et all(2012). Relationship between knowledge of ergonomics and work-place conditions with musculoskeletal disorders among nurses of two Iranian hospitals. tkj, 3(4) 19-25